Sospecha de glaucoma juvenil asociado a miopía de correlación. - Palma Rivera, Alexander Antonio (2020)
This case study was carried out in a 22-year-old girl who presents simple myopia, in the results of the complementary examinations anomalies were found that suggest a suspicion of juvenile glaucoma, this research is based on determining the glaucoma suspicions in relation to correlation myopia contributing data to future research carried out in the field of visual health. In which, according to detailed studies in this research, they affirm that people with myopia are more likely to develop glaucoma, generating visual impairment. Being a subject of much criticism and controversy since most of the population worldwide suffers from myopia; For this reason, the types of glaucoma, myopia and what their causes would be are described. Many authors give their opinion between the relationship of myopia with glaucoma in which they manifest the process that occurs in the internal structure of the eye so that this affectation is achieved.